Spatial variations in family planning demand to limit childbearing and the demand satisfied with modern methods in sub-Saharan Africa - Babayemi O. Olakunde; Jennifer R. Pharr; Daniel A. Adeyinka; Lung-Chang Chien; Rebecca D. Benfield; Francisco S. Sy (Reproductive Health, 2022)
Plain Language Summary In sub-Saharan Africa (SSA), studies have shown that the proportion of married women who want to stop having children has been increasing as well as the proportion using modern contraceptive methods among them. These studies also indicated that this proportion of women are higher in certain regions of Africa than the others. To extend these previous findings, we performed geographical analysis to assess how the proportion of married/in-union women who want to stop having children and the ones using modern methods among them differ geographically. Our findings indicated that neighboring countries where the proportion of married/in-union women who want to stop having children was higher than the overall average were concentrated in eastern and southern Africa (ESA), while neighboring countries in which the proportion of married/in-union women who want to stop having children was lower than the overall average were concentrated in western and central Africa (WCA). Similarly, the results also showed that neighboring countries where the proportion of married/in-union women using modern contraceptive methods among those who want to stop having children was lower than the overall average were concentrated in WCA. Our findings suggest that increasing joint decision making on family planning and uptake of antenatal care in SSA may improve the use of modern contraceptive methods among married/in-union women who want to stop childbearing.